Hereditary Spherocytosis with Splenomegaly and Cholelithiasis in a Young Male of Western Region of Nepal - A Case Report - Ghimire, P.; Gurung, N.V.; Shrestha, S.; Gurung, A.; Poudel, S.R.; Chapagain, A. (Kathmandu University Medical Journal, 2017)
See the PDF for the abstract.